It is two terms of an algebraic expression but if you mean -3 times -9 then it is 27
Chat with our AI personalities
It is two terms of an algebraic expression but if you mean -3 times -9 then it is 27
3x multiplied by (12x plus 9) is:3x(12x + 9)= (3x * 12x) + (3x * 9)= 36x2 + 27x
3x-y=9 y=3x-9
3x - 5 = 9 3x = 9 + 5 3x = 14 x = 14/3 or 4 2/3
3x-3 = 6 3x = 6+3 3x = 9 x = 3
The x-intercept is the point where the y-intercept is zero. "3x 5y 9" is not an equation. 3x+5y+9, or 3x-5y+9, are examples of what was meant to be shown.